Nonlinear dynamics in the jupiter magnetosphere: implications of dust-acoustic cnoidal mode. (23rd December 2021) - Tolba, R E; Yahia, M E; Moslem, W M
Abstract: Different types of waves and their nature in the Jovian middle magnetosphere are still not clear or specified. For this purpose, a generalized hydrodynamic model for an arbitrary amplitude dust-acoustic waves is built for true Jovian magnetosphere. The plasma system consists of positive dust grains, Maxwellian ions and electrons. An evolution equation containing a Sagdeev potential is derived, and its numerical analysis is presented. Unexpectedly, the given data yielded cnoidal waves only with positive potential. The effect of the external magnetic field, Mach number, and directional cosine parameters are studied and manipulated. We think that the present results are important in realizing the main waves in the Jovian magnetosphere, and the possible correlation to its particles' stability and pole acoustic waves.